2021
DOI: 10.18488/journal.aefr.2021.116.418.428
|View full text |Cite
|
Sign up to set email alerts
|

Working Capital Management and Performance of Six Deposit Money Banks in Nigeria

Abstract: Central to any financial institution's success is working capital management because mismanagement (WCM) can lead to its demise. This research examines the management of working capital in deposit money banks (DMBs) in Nigeria. This study evaluated the impact of liquidity on banks' performance to analyze how their competitiveness influences capital adequacy and assessed the correlation between loans and advances and deposit money banks' profitability. The study utilized a regression analysis, in which panel da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The result suggests that a greater emphasis on cash management within the operating cycle offers a more efficient approach to DWCM. These findings align with prior research conducted by Amponsah-Kwatiah and Asiamah (2020), who highlight a strong and significant positive association between CCC and both ROA and ROE, as well as Ailemen et al (2021), who assert that liquidity ratio and the capital adequacy ratio affect asset return significantly and positively.…”
Section: Impact Of Dwcm On Operating Profitsupporting
confidence: 90%
“…The result suggests that a greater emphasis on cash management within the operating cycle offers a more efficient approach to DWCM. These findings align with prior research conducted by Amponsah-Kwatiah and Asiamah (2020), who highlight a strong and significant positive association between CCC and both ROA and ROE, as well as Ailemen et al (2021), who assert that liquidity ratio and the capital adequacy ratio affect asset return significantly and positively.…”
Section: Impact Of Dwcm On Operating Profitsupporting
confidence: 90%
“…It revealed that Trade Receivable Period had a significant effect on the Returns on Assets, while Current ratio, Trade Payable and Inventory Conversion Period had an insignificant effect on Returns on Assets. It recommended that financial managers should set shorter credit period, negotiate with suppliers for an increase in payment period and monitor inventory levels so as to reduce the number of day inventories are held before they are sold Ikpefan, Osuma, Ahire, Evbuomwan, Kazeem & Chimezie (2021),. investigated working capital management and the performance of deposit money banks in Nigeria.…”
mentioning
confidence: 99%